Motivational predictors of language learning autonomy among ESL secondary school students in Malaysia. - Foroutan, Maryam; Noordin, Nooreen; Hamzah, Mohd Sahandri Gani (TextRoad Publication, 2013)
Drawing on self-determination theory (SDT), this study investigated secondary school students’ autonomy extent and the motivation orientation for learning English in Malaysia. The aim of this study was to explore the relationship between language learning autonomy and motivation in one of the eastern collectivist context, i.e. Malaysia. Going more in-depth, the relationship between more self-determined and less self-determined forms of motivation and autonomy in Malaysian context were explored. Additionally, by applying regression analysis categories of motivation which can predict language learning autonomy are determined.